Spinal cord Ewing's sarcoma metastasis: presentation of one case - Kara, G (Japanese Society Nuclear Medicine, 2004)
Cervical spinal Ewing's sarcomas are rare and cause problems in diagnosis. We present an unusual case of a primary extraosseous Ewing's sarcoma arising from the spinal cord. An 18-year-old woman with fever, headache and back pain lasting one month was admitted to the hospital. Whole body bone scintigraphy was performed with I 110 MBq technetium-99m methylenediphosphonate. Scintigraphy clearly showed abnormal technetium-99m methylenediphosphonate accumulation in the level of the 5th and 6th cervical vertebrae. Magnetic resonance imaging could also confirm this examination finding. After the scintigraphic study, the patient underwent surgery. Pathological diagnosis of the operation specimen was Ewing's sarcoma.
Keywords: extraosseous Ewing sarcoma; spinal cord; technetium-99m methylenediphosphonate bone scintigraphy